Analisis Penerapan Akuntansi Dan Kesesuaiannya Dengan SAK ETAP Pada UMKM: (Studi Kasus Desa Lau Dendang) - Muhammad Saleh Siregar; Nurlaila Nurlaila; Atika Atika (Jurnal Riset Akuntansi, 2024)
This study aims to determine how the application of accounting based on SAK ETAP. This research was conducted using a qualitative method with a descriptive approach. Data collection techniques in this study using observation, interviews and documentation techniques. The analysis technique used is using data reduction, data presentation and conclusion drawing. Based on data analysis, the results showed that several MSME players in Lau Dendang Village have not implemented SAK ETAP in running their businesses. MSMEs already have financial statement records but the records carried out are still simple.